Non-invasive prenatal testing (NIPT): reliability, challenges, and future directions - Jayashankar, Siva Shantini; Nasaruddin, Muhammad Luqman; Hassan, Muhammad Faiz; Dasrilsyah, Rima Anggrena; Shafiee, Mohamad Nasir; Ismail, Noor Akmal Shareela; Alias, Ekram (Multidisciplinary Digital Publishing Institute, 2023)
Non-invasive prenatal testing was first discovered in 1988; it was primarily thought to be able to detect common aneuploidies, such as Patau syndrome (T13), Edward Syndrome (T18), and Down syndrome (T21). It comprises a simple technique involving the analysis of cell-free foetal DNA (cffDNA) obtained through maternal serum, using advances in next-generation sequencing. NIPT has shown promise as a simple and low-risk screening test, leading various governments and private organizations worldwide to dedicate significant resources towards its integration into national healthcare initiatives as well as the formation of consortia and research studies aimed at standardizing its implementation. This article aims to review the reliability of NIPT while discussing the current challenges prevalent among different communities worldwide.